Use of Biocompatible Sorafenib-gold Nanoconjugates for Reversal of Drug Resistance in Human Hepatoblatoma Cells - Vishwakarma S.K.; Sharmila P.; Bardia A.; Chandrakala L.; Raju N.; Sravani G.; Sastry B.V.S.; Habeeb M.A.; Khan A.A.; Dhayal M. (My University, 2025)
The present study identifies the potential of highly biocompatible SF-GNP nano-conjugate to enhance the chemotherapeutic response to combat drug resistance in cancer cells. We developed a stable colloidal suspension of sorafenib-gold nanoconjugate (SF-GNP) of <10 nm size in aqueous medium for reverting the cancer drug resistance in SF-resistant HepG2 cells in a 3D ex-vivo model system. In-vivo biocompatibility assay of SF-GNPs showed absence of systemic toxicological effects including hematological, biochemical and histological parameters. More importantly, the histopathological analysis of vital organs such as liver, brain, lung, kidney and heart showed very least or no sign of inflammation, cell infiltration, necrosis, tissue disorganization or fibrotic reactions after intra-peritoneal administration of SF-GNP nanoconjugates in animals. However, SF-GNP nanoconjugates significantly reduced (>80%) the percentage cell survival and the size and number of SF resistant solid tumor colonies of HepG2 cells in 3D model system. The exposure of SF-GNP nanoconjugate to SF resistant HepG2 cell colonies also provided evidence for anti-proliferative effect and reversal of drug resistance by elucidating the molecular regulatory mechanisms of extracellular matrix factor (CD147), tumor growth factor (TGF-β), hepatoma upregulated protein (hURP) and drug transporter (ABCG-2). © 2017 The Author(s).